Effect of methyl substituent on the solubility of 1,4-benzoquinone derivatives in n-octanol/water system - Siti Mariyah Ulfa; Fath Dwisari; Ade Cintyia Sally; Mohammad Farid Rahman (Jurnal Kimia Sains dan Aplikasi, 2020)
The solubility of the compound is a crucial task for new drug design. Quinone is a promising candidate to develop as a new drug. In this research, the synthesis of 1,4-benzoquinone derivatives, that is, 2-(5-bromoamyl)-3,5-dimethyl-1,4-benzoquinone (2a) and 2-(5-bromoamyl)-5-methyl-1,4-benzoquinone (2b) were carried out by decarboxylation and insertion reaction of alkyl bromides. The product 2a and 2b are purified using SiO2 gel column chromatography and analyzed by UV-Visible, FT-IR, and NMR. The yield of 2a is 13.75%, and 2b is 4.04%. The solubility of 2a and 2b, expressed by log P, is measured in the n-octanol/water (3:7 (v/v)) system by the shake flask method. The log P of 2a and 2b are 2.99 and 1.36, respectively. It is showed that the log P of 2a is higher compared to 2b. The presence of two methyl substituents on the quinone ring of 2a supports the increase of hydrophobicity of the compound in the n-octanol/water system.